Orobanche bartlingii Griseb. (Orobanchaceae) in Poland: taxonomical position, distribution and habitat requirements - Piwowarczyk, Renata; Nobis, Marcin; Przemyski, Alojzy (Biodiversity: Research and Conservation, 2010)
The paper presents current distribution of Orobanche bartlingii Griseb. in Poland, including the new localities which were found in Podzamcze (Kraków-Częstochowa Upland) and Cząstków Stary (Kielce Upland). Taxonomical position as well as some diagnostic features that differ O. bartlingii from O. alsatica are presented. Habitat requirements and plant communities in which the species was recorded are discussed.